Omicron variants escape the persistent SARS-CoV-2-specific antibody response in 2-year COVID-19 convalescents regardless of vaccination. Issue 1 (31st December 2023) - Wang, Miao; Zhou, Bing; Fan, Qing; Zhou, Xinrong; Liao, Xuejiao; Lin, Jingyan; Ma, Zhenghua; Dong, Jingke; Wang, Haiyan; Ge, Xiangyang; Ju, Bin; Zhang, Zheng
ABSTRACT: With the ongoing COVID-19 pandemic and the emergence of various SARS-CoV-2 variants, a comprehensive evaluation of long-term efficacy of antibody response in convalescent individuals is urgently needed. Several longitudinal studies had reported the antibody dynamics after SARS-CoV-2 acute infection, but the follow-up was mostly limited to 1 year or 18 months at the maximum. In this study, we investigated the durability, potency, and susceptibility to immune evasion of SARS-CoV-2-specific antibody in COVID-19 convalescents for 2 years after discharge. These results showed the persistent antibody-dependent immunity could protect against the WT and Delta variant to some extent. However, the Omicron variants (BA.1, BA.2, and BA.4/5) largely escaped this preexisting immunity in recovered individuals. Furthermore, we revealed that inactivated vaccines (BBIBP-CorV, CoronaVac, or KCONVAC) could improve the plasma neutralization and help to maintain the broadly neutralizing antibodies at a certain level. Notably, with the time-dependent decline of antibody, 1-dose or 2-dose vaccination strategy seemed not to be enough to provide immune protection against the emerging variants. Overall, these results facilitated our understanding of SARS-CoV-2-induced antibody memory, contributing to the development of immunization strategy against SARS-CoV-2 variants for such a large number of COVID-19 survivors.